PERSPECTIVES ON RENEWABLE ENERGY IN SLOVENIA - Fouad Al-Mansour (Journal of Energy Technology, 2024)
The main strategic goals of the European Union (EU) and Slovenian energy strategies are the reduction of the emissions of greenhouses gases, an increase of the share of electricity production from renewable energy sources (RES) and a decrease of energy dependency. The overall targets of the EU climate and energy package, known as “20-20-20”, are a 20% increase in energy efficiency, a 20% reduction in greenhouse gas (GHG) emissions, a 20% share of renewable energy sources in overall EU final energy consumption, and a 10% share of renewable energy sources in transport by 2020. Individual targets for each Member State have to be determined as fairly as possible. The obligation of Slovenia is to increase the share of RES in final energy consumption from 15.1% in 2005 to 25% in 2020. Another obligation of Slovenia is to increase the share of electricity production from RES to 33.6% of the 2010 level total electricity consumption. The priority to increase the share of RES in the energy supplies in the EU-27 has continued moreintensively to avoid the rapid impacts on environment (climate change) and to increase the security and sustainability of energy supply. In 2008, the share of renewable energy in primary energy was less than 11%, and it was 15.1% in gross final energy consumption. The share of electricity production from renewable energy sources represents 30% of gross electricity consumption in Slovenia. The development of renewable energy sources in Slovenia as well as an analysis of the Slovenian energy policy will be presented in this paper. Special focus will be given to the actual programs (RES action plan) and the potential of future development.